2021
DOI: 10.7150/jca.62332
|View full text |Cite
|
Sign up to set email alerts
|

GALNT6 Knockdown Inhibits the Proliferation and Migration of Colorectal Cancer Cells and Increases the Sensitivity of Cancer Cells to 5-FU

Abstract: The incidence of colorectal cancer (CRC) is increasing annually worldwide, highlighting the need for novel therapeutics to be developed. GALNT6 is a member of the N-acetylgalactosyltransferase enzyme family, which exhibits oncogenic functions in several types of cancers, such as breast cancer and ovarian cancer. However, the function of GALNT6 in CRC has not received much attention in recent years and is therefore poorly understood. In this study, the GALNT6 gene was screened using RNA-seq data obtained from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Recent studies have reported that GALNT6 is highly upregulated in CRC tissues. 45 , 46 In addition, GalNAc‐Ts have been reported to influence several tumorigenic processes, including immune evasion, invasion, EMT induction, and metastasis. 46 , 47 , 48 Moreover, a low expression of TFF2 and TFF3, which were predicted to be inhibited by GALNT6, have been reported to associate with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that GALNT6 is highly upregulated in CRC tissues. 45 , 46 In addition, GalNAc‐Ts have been reported to influence several tumorigenic processes, including immune evasion, invasion, EMT induction, and metastasis. 46 , 47 , 48 Moreover, a low expression of TFF2 and TFF3, which were predicted to be inhibited by GALNT6, have been reported to associate with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis predicted that GALNT6 (polypeptide N‐acetylgalactosaminyltransferase 6; GalNAc‐T6) was activated in EOCRC where it inhibited ANPEP expression. Recent studies have reported that GALNT6 is highly upregulated in CRC tissues 45,46 . In addition, GalNAc‐Ts have been reported to influence several tumorigenic processes, including immune evasion, invasion, EMT induction, and metastasis 46–48 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, COL9A3 promotes epithelial-to-mesenchymal transition, invasion, and migration in gastric cancer (Wu et al, 2021). GALNT6 overexpression has been associated in CRC with resistance to fluoropyrimidines and CRC cell proliferation and migration (Peng et al, 2021). This gene is also involved in the activation of the PI3K/AKT signaling pathway and in breast cancer cell migration and invasion (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics studies can often produce more accurate results for microarray testing of glioma samples based on large sample data. According to recent research, the expression of the GALNT6 gene has been linked to the proliferation, migration, and drug sensitivity of tumors 13 .…”
Section: Introductionmentioning
confidence: 99%